The Effects of Macroeconomics Indicators and Institution Quality on the FDI of 5 Developing Countries in Asean - Rahayu, Shauqy Dwi; Saputra, Putu Mahardika Adi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2026)
Foreign Direct Investment (FDI) is a key component in promoting a country’s economic development, influenced by several factors, including macroeconomic indicators and institutional quality. This study examines the effect of macroeconomic indicators (GDP and exchange rate) and institutional quality (government effectiveness and control of corruption) on FDI in five developing ASEAN countries (Indonesia, Thailand, Malaysia, Vietnam, and the Philippines) over the past 22 years (2002–2023). A quantitative approach is employed using panel data regression with a Fixed Effect Model (FEM). The data used are obtained from official sources, specifically the World Bank. The results indicate that GDP, government effectiveness and Control of Corruption have a significant positive impact on FDI. In addition, the Exchange Rate also shows a significant impact, but in a negative direction.